1977
DOI: 10.2307/2387877
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Growth of Red Mangrove (Rhizophora mangle L.) 4. The Adult Root System

Abstract: Aerial roots in Rhizophora arise from stems, branches, and secondarily thickened, anchored, aerial roots, but only after injury from unanchored aerial roots. Lateral subterranean roots are abundantly developed upon penetration of a mud substrate whereupon the histology of the root undergoes marked and abrupt changes so that chlorophyll is no longer developed, trichosclereids no longer differentiate, tannin cells become few, the cortex becomes markedly lacunose, and the sequence of protoxylem differentiation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1
6

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 10 publications
1
70
1
6
Order By: Relevance
“…Note root repair was found to occur substantially more frequently than lateral root initiation, assuming that 100% of the lateral roots were initiated in response to burrowing. Past studies have found that lateral root production does not occur or is extremely rare unless triggered by injury (Gill & Tomlinson 1977, Perry & Brusca 1989. However, if not all lateral roots were produced as a result of burrowing, mangrove response to attack via burrow repair is even more biased toward burrow repair than lateral root initiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note root repair was found to occur substantially more frequently than lateral root initiation, assuming that 100% of the lateral roots were initiated in response to burrowing. Past studies have found that lateral root production does not occur or is extremely rare unless triggered by injury (Gill & Tomlinson 1977, Perry & Brusca 1989. However, if not all lateral roots were produced as a result of burrowing, mangrove response to attack via burrow repair is even more biased toward burrow repair than lateral root initiation.…”
Section: Resultsmentioning
confidence: 99%
“…The 2 herbivore response strategies (i.e. avoidance and tolerance) may not be mutually exclusive, however, and some species may demonstrate levels of both (Fineblum & Rausher 1995, Mauricio et al 1997.The red mangrove Rhizophora mangle L. produces aerial prop roots from the bole, trunk, and other aboveground roots which grow down through the water column and eventually attach to the substratum (Gill & Tomlinson 1977). The aerial portion of these prop roots has secondary vascular development and thick surface cells that are not found in the subterranean part of the root once it attaches (Gill & Tomlinson 1975).…”
mentioning
confidence: 99%
“…The authors conclude their study by emphasizing features which are not found in dicotyledonous roots, and which are considered exceptions in the roots of Rhizophora mangle: polyarch stele, wide pith, the collateral position of the vascular tissues, and endarch protoxylem. In a later study, Gill and Tomlinson (1977) also mention that these " aerial roots" originate in the trunk, or in other " aerial roots", sympodially, but never in underground (or submerged) roots. The results presented in this study indicate that the aerial branch system of Rhizophora mangle, with positive geotropism, is, in fact, a rhizophorous system which is very similar to a stem system with negative geotropism, as perfectly demonstrated in Table I of the present work.…”
Section: Discussionmentioning
confidence: 95%
“…Damage to prop roots may also occur from physical actions such as abrasion (Gill & Tomlinson, 1977), or by falling branches from the canopy. Debris brought in by the tides and extreme storm events may also damage mangrove roots (McIvor et al, 2013;Jusoff, 2013), which are predicted to increase (Bhatt & Kathiresan, 2012).…”
Section: Introductionmentioning
confidence: 99%